(untitled) (Journal of Informatics Education and Research, 2025)
Technological literacy has now become a necessitate to education and employment in the fast- paced digital era and social life. This research will evaluate the current level of digital literacy and technological proficiency of Karnataka youth populations, identify the barriers that make them physically inaccessible to digital inclusion and offer viable solutions to enhance their digital literacy and proficiency. Structured questionnaires and descriptive study design were used in the collection of 100 respondents in various districts. The study found out that even though a large percentage of the young generation has basic computer and smartphone knowledge, the advanced digital literacy level including data management, digital collaboration, cybersecurity awareness, and the adoption of new technologies is still considerable. The paper will conclude by stating that special training initiatives, government-business partnership, and integration of digital skills training modules into the official curriculum can make the Karnataka youth workforce and enhance inclusive digital development significantly. The research concludes that inclusive digital education, the improvement of internet access in rural communities, and the incorporation of ICT- based training into the educational programs are the key measures that may be implemented to empower digital skills. Such programs can overcome the digital divide and make the youth in Karnataka be able to be active members of a technology driven world.